Ministry of Tourism Decree No. 1053 of The year 2015 Issued on 20/2/2015 Cancelling D. No. 381 and D. No. 1281/2014 Concerning Obliging Tourist Companies that own tourist buses to install security cameras in their buses = قرار وزير السياحة رقم 1053 لسنة 2018 بإلغاء القرارين رقمي 381 و 1281 لسنة 2014 بشأن كاميرات المراقبة في الحافلات السياحية / Ministry of Tourism - Egypt. Ministry of Tourism (2025)
Ministry of tourism decree no. 1053 of the year 2015 issued on 20/8/2015 وزارة السياحة قرار رقم 1053 لسنة 2015 صادر بتاريخ 20/8/2015